Sustainable farmland management: transdisciplinary approaches - Fish, R.; Fish, R.; Seymour, S.; Seymour, S.; Steven, M.; Steven, M.; Watkins, C.; Watkins, C. (Wallingford :CABI, 2008)
This edited collection is an exercise in transdisciplinary reflection on sustainable farmland management. It includes contributions from leading academics and emerging researchers from a range of disciplinary backgrounds including economics, agricultural sciences, geography and environmental sciences, as well as practitioners and researchers from NGOs, government agencies and consultancies, who are involved in informing policy and practice on sustainable agricultural landscapes. The first part (chapters 2-6) maps out the territory of sustainable farmland management in differing spatial, temporal and production contexts. The second part (chapters 7-10) examines the disputed arena of knowledge claims for sustainable farmland management and considers different styles of knowledge deployed in a range of contexts. The third part (chapters 11-13) focuses more explicitly on the ethics of farmland production and protection, on their connections with debates over sustainability and calls for new ethical frameworks. The fourth part (chapters 14-18) examines a range of key issues surrounding systems and systemic thinking for sustainable farmland management, including the scales of application and measurement of systems approaches and the benefits and drawbacks of different farmland management systems. The final part (chapters 19-22) reflects directly upon some of the emerging political and policy frameworks now governing the idea of sustainable farmland management. The book has a subject index.
Keywords: EE110 - Agricultural Economics; EE115 - Natural Resource Economics, (New March 2000); EE120 - Policy and Planning; PP300 - Land Resources; UU485 - Social Psychology and Social Anthropology, (New March 2000)